2012
DOI: 10.1074/jbc.m112.340612
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structure Determination of Novel Anti-inflammatory Mediator Resolvin E3, 17,18-Dihydroxyeicosapentaenoic Acid

Abstract: Background: Endogenous mediators that control aberrant inflammation are of interest as potential targets of new therapeutics.Results: Here, we identified a novel omega-3 fatty acid-derived anti-inflammatory mediator 17,18-diHEPE, denoted as resolvin E3.Conclusion: Resolvin E3 has a potent inhibitory action on neutrophil chemotaxis both in vitro and in vivo.Significance: The significance of this study is the identification of a novel endogenous lipid mediator with a potent anti-inflammatory property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
180
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(186 citation statements)
references
References 27 publications
1
180
1
Order By: Relevance
“…There are few data attesting to their formation in humans based on rigorous mass spectrometric methodology. Most clinical investigations reporting the formation of SPMs rely on immunoassays ( 21 ) or MS without synthetic internal standards structurally similar to the SPMs under investigation (22)(23)(24)(25)(26)(27)(29)(30)(31)(32), often in ex vivo stimulated systems ( 17,(33)(34)(35)(36).…”
Section: Blood (Rbc Membranes) For the Study High Doses Of Lovaza Fishmentioning
confidence: 99%
“…There are few data attesting to their formation in humans based on rigorous mass spectrometric methodology. Most clinical investigations reporting the formation of SPMs rely on immunoassays ( 21 ) or MS without synthetic internal standards structurally similar to the SPMs under investigation (22)(23)(24)(25)(26)(27)(29)(30)(31)(32), often in ex vivo stimulated systems ( 17,(33)(34)(35)(36).…”
Section: Blood (Rbc Membranes) For the Study High Doses Of Lovaza Fishmentioning
confidence: 99%
“…4B , 12-HETE). Recently, Isobe et al reported that HEK293 cells produced a signifi cant amount of 12-HETE after incubation with 10 µM arachidonic acid ( 25 ), suggesting that excess arachidonic acid is converted to 12-HETE in HEK293 cells, possibly by endogenous 12-lipoxygenase. Figure 4 suggests that TxAS is dispensable for 12-HHT production but indispensable for TxB 2 production in COX-1-expressing cells.…”
Section: Production Of 12-hht and Txb 2 In Human Plateletsmentioning
confidence: 99%
“…RvE3 was biosynthesized from EPA by P450 or aspirin-acetylated cyclooxygenase-2, followed by 15-lipoxygenase activity. 25 TNF-α stimulation had no effects on lipoxygenase expression, and EPA-rich rHDL induced RvE3 production, suggesting that RvE3 production is directly reflected by the amount of EPA. Surprisingly, the HDL structure appeared to be necessary for the efficient conversion of EPA-PC to 18-HEPE and RvE3 by endothelial cells.…”
Section: Preparation and Characterization Of Rhdlmentioning
confidence: 88%